Investigation of Macadamia Flour Fortified to Wheat Flour in Bread Making - Minh Phuoc Nguyen (Journal of Global Pharma Technology, 2016)
Bread is one of the most important staple foods in the world. Macadamia nut contains bioactive components and high levels of monounsaturated fatty acids that are beneficial to human health. It would be of therapeutic advantage if wheat flour could be replaced with phytochemical functional nuts other than wheat flour such as macadamia in bread-making. This research has been tried in the application of composite flour through the incorporation of macadamia flour into wheat flour to improve nutritional quality of bread. In this study, macadamia ﬂours were used to substitute refined wheat ﬂour in bread-making doughs at 2%, 4%, 6%, 8%, 10% substitution levels. Significant variations in physicochemical, biological and organoleptic attributes were thoroughly noticed. The substituted bread-making with 8% macadamia flour had enhanced firmness, rich in total phenolics, ﬂavonoids but low in peroxide value. During 8 days of preservation in paper- aluminum foil polyethylene laminate pouch at ambient temperature, the physico-chemical, microbial and sensory characteristics of bread still conformed to overall acceptability.Keywords: Bread, Macadamia, Firmness, Phenolic, Flavonoid, Peroxide value.